10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Buffalo can efficiently convert fibrous materials into energy and produce milk and meat in harsh conditions that other ruminants cannot survive. OBJECTIVES: This study was conducted to investigate the effect of olive pomace (OP) on the quality of buffalo milk and yogurt and to improve its characteristics for human health. METHODS: Fifteen lactating buffaloes have been used with an average age of 4 ± 1 years and a weight of 570 ± 40 kg. Treatments of 0%, 7.5%, and 15% olive pomace substituted with wheat flour, which was fed two times for 45 days in a completely randomized design (3 treatments, 5 replicates). Milk from each animal was used to test milk composition and microbial load. The fatty acid profile of milk and yogurt composition of all buffaloes was measured. Data were analyzed by completely randomized design in SAS. RESULTS: Results showed that milk fat and SNF (solids not fat) increased in olive pomace treatments (p < 0.05), but milk production, protein, and pH were not different (p > 0.05). The acidity, microbial load, Staphylococci, and SNF of yogurt produced from buffalo's milk were not influenced by treatments (p > 0.05). Yogurt fat significantly decreased (p < 0.05) in OP7.5 and significantly increased (p < 0.05) in OP15 buffaloes. Protein concentration in yogurt dropped by olive pomace diets, and coliforms were the highest for OP15 olive pomace (p < 0.05). The concentration of short and medium-chains fatty acids (C4:0, C8:0, C10:0, C12:0), linolenic acid, and conjugated fatty acids (CLA isomers) of buffalo's milk in OP15 is more than in other treatments (p < 0.05). The replacement of olive pomace with wheat flour increased milk production of dairy buffaloes. The concentration of short and medium-chain fatty acids and unsaturated and conjugated fatty acids increased in OP15 buffalo. Furthermore, a lower saturated/unsaturated ratio and atherogenic index suggest an improvement in the nutritional characteristics of milk buffaloes. Therefore, it's recommended in the diet of dairy buffaloes. CONCLUSIONS: Therefore, due to the proper price of olive pomace, its replacement with wheat flours up to 15% in lactating buffaloes is recommended. But still, it needs further research to prove olive pomace efficacy on milk and yogurt quality in buffaloes.